2012
DOI: 10.1037/a0031676
|View full text |Cite
|
Sign up to set email alerts
|

Frontier no more: International consulting skills as necessary minimal competencies for consulting psychologists.

Abstract: This article identifies and comments on several themes that derive from the Special Issue on International Organizational Consulting: Consulting Psychology Goes Global. Six issues are identified that are intended to help integrate the Special Issue articles and to extend the four factors each article addressed: (1) how can we generalize from cases to actionable propositions?; (2) does corporate culture trump national culture?; (3) Is country an individual difference variable?; (4) are there international metac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Without such training, school psychologists will continue to operate in a direct service model. Lowman (2012), in a special CPJ issue on international organizational consulting, suggested that international organizational consulting should become less noted "for its exceptionalness and more a common part of practice and education for practice" (p. 341). Cooper (2012), Editor of the special issue, invited the issue authors to focus on whether there are "issues specific to international organizational consulting psychology different from those addressed by existing cross-cultural findings" (p. 245).…”
Section: Implementation Of Interventionsmentioning
confidence: 99%
“…Without such training, school psychologists will continue to operate in a direct service model. Lowman (2012), in a special CPJ issue on international organizational consulting, suggested that international organizational consulting should become less noted "for its exceptionalness and more a common part of practice and education for practice" (p. 341). Cooper (2012), Editor of the special issue, invited the issue authors to focus on whether there are "issues specific to international organizational consulting psychology different from those addressed by existing cross-cultural findings" (p. 245).…”
Section: Implementation Of Interventionsmentioning
confidence: 99%
“…The fact that many organizations, both large and small, are international in scope presents significant challenges for the experienced consultant-even more so for the newly minted consultant who has to consider both his or her consulting and international inexperience. Lowman (2012) has even suggested international consulting skills as minimal competencies for consultants because "specific locations even in isolated and would-be quiescent organizations in rural areas can still experience the impact of having to contend with internationally influenced issues" (p. 339).…”
Section: The Consulting Settingsmentioning
confidence: 99%
“…This 2012 special issue also noted that although expert observations via case studies are important, an overarching need exists for more empirical research and theory development to inform consultative practice. This need remains and is more necessary than ever because although the majority of consulting psychologists may work exclusively in their home country, the continued globalization of the work and marketplace means that consultation is likely to touch on international issues, requiring all consulting psychologists to develop basic competencies in international consulting (APA, 2017b;Fulkerson, 2012;Lowman, 2012).…”
mentioning
confidence: 99%